2021
DOI: 10.1111/head.14198
|View full text |Cite
|
Sign up to set email alerts
|

The evolving understanding of risk with calcitonin gene‐related peptide monoclonal antibodies based on real‐world data: A focus on hypertension and Raynaud phenomenon

Abstract: How to cite this article: Breen ID, Mangold AR, VanderPluym JH. The evolving understanding of risk with calcitonin gene-related peptide monoclonal antibodies based on real-world data: a focus on hypertension and Raynaud

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…22 Given the unpredictable natural course of RP, the authors comment that it is hard to say whether these individuals would have developed RP regardless of exposure to CGRP monoclonal antibodies. 23 The following cases suggest a possible relationship between RP and gepant treatment in two patients. One individual experienced RP with both ubrogepant and rimegepant for acute treatment.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…22 Given the unpredictable natural course of RP, the authors comment that it is hard to say whether these individuals would have developed RP regardless of exposure to CGRP monoclonal antibodies. 23 The following cases suggest a possible relationship between RP and gepant treatment in two patients. One individual experienced RP with both ubrogepant and rimegepant for acute treatment.…”
mentioning
confidence: 85%
“…These complications ranged from worsening of underlying RP to necessitating distal digit amputation due to gangrene and autonecrosis 22 . Given the unpredictable natural course of RP, the authors comment that it is hard to say whether these individuals would have developed RP regardless of exposure to CGRP monoclonal antibodies 23 …”
Section: Introductionmentioning
confidence: 99%
“…Due to the vasodilatory action of CGRP particular attention has been paid to the potential effects on blood pressure [23]. Clinical trials did not show a significant risk of hypertension with erenumab but it has been reported in post-marketing surveillance [24,25] and is now included as a warning on the package insert in the US [26]. We found a statistically significant rise in systolic BP following 3 months of erenumab treatment but the magnitude of this was very small (2.4 mmHg) and therefore of questionable clinical significance.…”
Section: Tolerability Of Erenumabmentioning
confidence: 99%
“…Safety data for the use of monoclonal antibodies in these patient groups are not yet available. Therefore, in the following conditions, the use of monoclonal antibodies against CGRP or the CGRP-receptor should be considered only on a case-by-case basis after detailed consideration of potential risks and the potential benefits: Pregnancy and lactation, subarachnoid hemorrhage [57], familial aneurysms, inflammatory bowel disease [58], gastrointestinal ulcers, stroke [57], TIA, coronary artery disease, poorly controlled hypertension [59], Raynaud's disease [60][61][62], COPD, pulmonary hypertension, wound healing disorders [63], and psoriasis [64].…”
Section: Drug And/or Non-drug Prophylaxis For the Treatment Of Mohmentioning
confidence: 99%